Tinjauan Kitab Undang-Undang Hukum Pidana (KUHP) Baru 2023 - Malau, Parningotan (Fakultas Syariah INSURI Ponorogo, 2023)
The purpose of this research is to examine the new Criminal Code (KUHP) introduced in 2023. The research methodology used is a juridical-empirical approach, employing a descriptive research design to provide an overview of the newly enacted KUHP by the President on January 2nd, 2023. The problem-solving approach in this study is descriptive, aiming to describe and analyze the new KUHP. To address the research problem, secondary data analysis was conducted through an extensive review of literature, including relevant legal materials and legislation. The research then proceeded to analyze the collected data using qualitative methods, drawing insights from the existing literature and legal provisions. The findings of this research indicate that the endorsement of the new KUHP by the President and the People's Consultative Assembly (DPR RI) marks a significant milestone in the development of the criminal justice system in Indonesia. With these changes, it is expected that law enforcement will become more effective, justice will be better upheld, and human rights will be protected more comprehensively. Looking towards the future, the amendments to the KUHP should continue to address emerging challenges to remain relevant and provide significant benefits to Indonesian society. In conclusion, the enactment of the new KUHP is a crucial step in strengthening the criminal justice system in Indonesia. However, effective implementation, monitoring, and periodic review remain challenges that need to be addressed. Through the commitment and collaboration of all stakeholders, it is hoped that the new KUHP will serve as an effective instrument in promoting justice, protecting human rights, and enhancing law enforcement in Indonesia.